Las vidrieras de la Catedral de Jaén - Casuso Quesada, Rafael (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2018)
El estudio de las vidrieras de la Catedral de Jaén nos lleva a establecer dos tipos: el de las translúcidas, correspondientes al gusto clasicista de los siglos XVI al XVIII, y el de las decorativas, de principios del siglo XX. Carecemos de noticias documentales acerca del pensamiento del arquitecto Andrés de Vandelvira en su proyecto original, si acorde con los programas goticistas ejecutados por entonces en otras catedrales españolas o afín a las nuevas ideas de iluminación «blanca» del Renacimiento italiano. Un estudio del inventario de bienes efectuado a su fallecimiento nos revela la posesión de dos libros del tratadista Sebastiano Serlio, quien ya apostaba por el empleo de vidrieras geométricas, no decorativas. La constatación de esta nueva estética en los continuadores de la obra de Vandelvira es evidente. Una comparación del efecto lumínico entre las vidrieras clasicistas y las historicistas nos da idea de dos concepciones abismales del tratamiento de la luz. A study of stained glasses in Jaen´s Cathedral leads us to distinguish two different types: the transparent ones, corresponding to the classicist taste from the XVI-XIX centuries on the one hand and the ornamented or stained ones, dating back from the beginning of the XX century, on the other. Unfortunately we lack information from Vandelvira´s --the main architect of the Cathedral--original project: whether it was according to the gothic prevalent ideas, which were carried out in many of the Spanish cathedrals at that time, or embraced the new ideas from the Italian Renaissance, which were in favour of a «white light» instead. A survey of the inventory of his goods, made after he died, reveals that Vandelvira was in possession of two of Sebastiano Serlio´s books on architecture. They show that Serlio was in favour of using transparent glasses. The verification of this new aesthetic in the followers of the work of Vandelvira is evident. A comparison of the luminous effect between classicist stained-glass windows and historicist windows gives us the idea of two totally opposed conceptions of the treatment of light.